Emblems of Faith: Holy Companions on the Road to Observance - FLOREA, Carmen (Studia Universitatis Babeș-Bolyai Historia, 2023)
The present study focuses on the specific devotional models that were promoted by the Observant Dominican friars in the late Middle Ages. By closely investigating textual and visual sources, previous research has noted that the reformed friars were eager to disseminate, particularly within the communities of the Observant Dominican women, the cult for the Passion of Christ and cults of saints that were easily transformed into models that pious women would adopt and emulate. Since the Observance was an European phenomenon and strong contacts existed between local friars and influential centres of reform, the prerequisites of the Dominican forma vitae became the standard according to which the communities of Observant Dominican women were organized and functioned. An integral part of this process of standardisation concerned the holy companions of the pious women affiliated to the Order of the Friars Preachers, who were usually recruited from the same cohort of saints represented by the Virgin Martyrs. Rezumat: Studiul de față investighează modele devoţionale care au fost promovate cu predilecție de către Dominicanii Observanţi în perioada evului mediu târziu. Analiza detaliată a surselor textuale şi vizuale produse în ambianță observantă a evidențiat faptul că devoţiunea cristocentrică şi cultele unor sfinţi care puteau fi ușor transformate în modele imitabile au fost susţinute şi diseminate de către fraţii dominicani, îndeosebi în comunităţile călugăriţelor dominicane observante. Mişcarea observantă, un fenomen european, a facilitat răspândirea unor formule specifice care caracterizau modul de viață în cadrul ordinului, de multe ori intermediarii acestei diseminări fiind fraţi din regiune care au studiat în centre ale reformei observante (universităţi sau conventuri). Procesul de uniformizare și standardizare care a organizat mănăstirile călugăriţelor dominicane a inclus şi adoptarea unor culte specifice, integrate modelului de sanctitate virginală şi martirală. Cuvinte cheie: mişcare observantă; Ordinul Fraților Predicatori; călugărițe dominicane; devoțiune christocentrică; cultul sfinților Article: history; Received: 15.05.2023; Revised: 17.05.2023 Accepted: 10.06.2023; Available online: 30.06.2023.